Social media advertising as strategy on consumer buying behaviour: conceptual paper - Kumaradeepan, V. (University of Jaffna, 2020)
Social media advertising has rapid speed of change in the every industry generated the need to create, adapt and integrate conversations that will allow bridging the gaps between the brand and consumers. The objective of this study is to investigate theoretical evidences of the concept of Social media advertising and its impact on consumer buying behaviour in order to develop customer relationships. This is done by communicating, engaging, entertaining and triggering response through social media content to ultimately stage and develop a customer experience which will make sure the development a long-term relationship and immersing the brand within the consumer’s lifestyle. Moreover the study has various properties of social media marketing in regards to media platforms.
Keywords: Advertising; Buying behaviour; Consumer behaviour; Social edia